Growth and Yield of Red Rice (Oryza nivara L.) Applied with Organic and Inorganic Fertilizers - Septi Lora Aulia; Maria Fitriana; Erizal Sodikin (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2021)
Red rice was one species of rice in Indonesia that was superior in nutritional content and selling price compared to white rice but the productivity of red rice is still low. One of way to improved rice growth and productivity is fertilization red rice was one type of rice in Indonesia that contains high nutrition. This research aimed to observe the effects of the combination of organic and inorganic fertilizers on the growth and yield of red rice (Oryza nivara L.). The research used a Randomized Completely Block Design (RCBD) with 7 treatments. Each treatment had 3 replications and each experiment unit consisted of 3 plants so that there were 63 plants. The best treatment was compost of oil palm empty fruit bunch (125 g) + N, P, and K fertilizer 50%. The highest production was on oil palm empty fruit bunch compost (125 g) + Fertilizer N, P and K 50%, it was equivalent to 5.49 ton/ha. In the red rice crop farming system it can be recommended to provide a combination of oil palm empty fruit bunch (125 g) compost and 50% N, P and K fertilizer to increase yields in the cultivation of red rice.